(untitled) (Acta Scientiarum. Animal Sciences, 2018)
Heritability and direct and maternal genetic changes were estimated in Nellore cattle for the following traits: birth to weaning weight gain (BWG), weaning to yearling weight gain (YWG), weaning conformation (WC), weaning precocity (WP), weaning muscling (WM), yearling conformation (YC), yearling precocity (YP), yearling muscling (YM) and yearling scrotal circumference (SC). Direct and maternal heritability for weaning traits were 0.21±0.03 and 0.13±0.01 (BWG); 0.19±0.03 and 0.07±0.01 (WC); 0.22±0.03 and 0.07±0.01 (WP); 0.20±0.03 and 0.07±0.01 (WM), respectively. For yearling traits, direct heritability were 0.19±0.04 (YWG); 0.32±0.05 (YC); 0.37±0.05 (YP); 0.38±0.05 (YM) and 0.41±0.04 (SC). Positive and significant direct genetic changes (p < 0.05) were found for all traits, except for WC (p = 0.09), equal to 0.138 kg year-1 (BWG), 0.003 units year-1 (WC), 0.011 units year-1 (WP), 0.009 units year-1 (WM), 0.132 kg year-1 (YWG), 0.003 units year-1 (YC), 0.011 units year-1 (YP), 0.011 units year-1 (YM) and 0.020 cm year-1 (SC), indicating favorable genetic gains in the period. For weaning traits, we obtained negative and non-significant (p > 0.05) maternal genetic trends, with values of -0.084 kg year-1 (BWG), -0.004 units year-1 (WC), -0.004 units year-1 (WP) and -0.004 units year-1 (WM). Thus, greater emphasis should be given for maternal genetic merit of weaning traits in this population, if improvements in maternal ability were desirable.